2016
DOI: 10.1007/s00296-016-3518-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of nursing clinics in the rheumatology services

Abstract: Nursing clinics in rheumatology (NCRs) are organisational care models that provide care centred within the scope of a nurse's abilities. To analyse the impact of NCR in the rheumatology services, national multicenter observational prospective cohort studied 1-year follow-up, comparing patients attending rheumatology services with and without NCR. NCR was defined by the presence of: (1) office itself; (2) at least one dedicated nurse; and (3) its own appointment schedule. Variables included were (baseline, 6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 22 publications
0
30
0
5
Order By: Relevance
“…Additional evidence from RCTs supported positive effects on pain, fatigue, illness perception, quality of life and sedentary time from nurse-led patient educational programmes and involvement of nurses in self-regulation coaching in a multicomponent, action-focused intervention 35 38. Moreover, cohort studies and one cross-sectional study presented the beneficial outcomes of nurse-led patient education, such as the development of more and timely educational activities for patients, improving patients’ adherence to treatments 39–44…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional evidence from RCTs supported positive effects on pain, fatigue, illness perception, quality of life and sedentary time from nurse-led patient educational programmes and involvement of nurses in self-regulation coaching in a multicomponent, action-focused intervention 35 38. Moreover, cohort studies and one cross-sectional study presented the beneficial outcomes of nurse-led patient education, such as the development of more and timely educational activities for patients, improving patients’ adherence to treatments 39–44…”
Section: Resultsmentioning
confidence: 97%
“…The level of evidence was high for this recommendation and it was further strengthened by two meta-analyses and one RCT with long-term follow-up 3 8 37 55. These studies and additional RCTs that compared nurse-led and physician-led follow-up, and cohort studies, showed that nurse-led care resulted in equivalent or improved control of disease activity in patients with RA 6 8 16 37 42 55 56. Nurse-led care was cost neutral or slightly less costly than physician-led care but no evidence for cost savings was found 14 16 57–59.…”
Section: Resultsmentioning
confidence: 99%
“…Cost reductions were reported together with stable outcome parameters in monitoring CIA-outpatients with stable and low disease activity under treatment with biological agents, with a nurse taking over every second visit of the rheumatologist [ 39 ]. Authors from different European countries performed economic analyses of various forms of nurse-led care, and the majority of economic analyses investigated an established nurse-led model of care [ 17 , 26 , 39 , 40 ] provided by specialised nurses [ 17 , 39 41 ]. Although nurse consultation costs were lower than physicians’ costs, there was only few evidence that nurse-led care decreases total costs compared to physician-led care [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors identified 657 publications: 52 were selected for detailed review (Figure 1). Twenty papers were included: seven qualitative studies (242 patients) (Arvidsson et al, 2006; Bala et al, 2012; Larsson, Bergman, Fridlund, & Arvidsson, 2012; Long, Kneafsey, Ryan, & Berry, 2002; Primdahl, Wagner, & Horslev‐Petersen, 2011; Temmink, Hutten, Francke, Abu‐Saad, & van der Zee, 2000; van Eijk‐Hustings et al, 2013), nine clinical trials (2,440 patients) (Dougados et al, 2015; Hill, Thorpe, & Bird, 2003; Koksvik et al, 2013; Larsson, Fridlund, Arvidsson, Teleman, & Bergman, 2014; Ndosi et al, 2014; Primdahl, Sorensen, Horn, Petersen, & Horslev‐Petersen, 2014; Ryan, Hassell, Lewis, & Farrell, 2006; Symmons et al, 2005; Tijhuis et al, 2002) and four observational studies (1,234 patients) (Esselens, Westhovens, & Verschueren, 2009; Munoz‐Fernandez et al, 2016; Solomon et al, 2015; Watts et al, 2015), two with cohort and two with case–control designs. Details of these studies are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Fewer patients in practices with nurses or physician assistants had high disease activity levels, indicating better standards of care. Munoz‐Fernandez et al (2016) compared rheumatology services with nursing clinics in rheumatology and services without. The nursing clinics had at least one dedicated nurse with her own appointment schedule.…”
Section: Resultsmentioning
confidence: 99%